Synergy of Islamic Religious Education and Digital Technology in Realizing 21st Century Learning - Imamah, Yuli Habibatul (International Journal on Advanced Science, Education, and Religion, 2025)
The 21st century is marked by rapid advancements in digital technology, necessitating a paradigm shift in the field of education, including Islamic Religious Education (IRE). This study aims to analyze how the synergy between IRE and digital technology can create learning experiences that align with the demands of the 21st century. The research identifies three key aspects: the integration of digital technology into IRE instruction, innovation in digital-based learning media, and the role of digital literacy in shaping students' Islamic character. Utilizing a descriptive qualitative approach through library research, data were collected from academic literature, journal articles, and Islamic education policy documents. The findings indicate that the incorporation of technology in IRE enables more contextual and relevant learning experiences for digitally engaged students. Innovations such as interactive videos, podcasts, and Islamic applications enhance student engagement and deepen their understanding of religious values. Furthermore, Islamic digital literacy serves as a critical foundation for equipping students to interact in the digital space with ethical, critical, and responsible behavior. This synergy presents an effective strategy for nurturing a generation of Muslims who are not only technologically literate but also spiritually grounded and morally upright in navigating contemporary challenges.